Non-aqueous electrolyte and lithium ion battery

JP2025021396AActive Publication Date: 2025-02-13ENVISION DYNAMICS TECH (JIANGSU) CO LTD +4
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023215094
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-31
Filing Date
2023-12-20
Publication Date
2025-02-13
Estimated Expiration
2043-12-20

AI Technical Summary

Benefits of technology

【0018】 本発明は、クロロエチレンカーボネート(ClEC)及びジフルオロビス(オキサラト)リン酸リチウム(LiODFP)である塩素含有有機添加剤を非水電解液に導入する。導入過程において、クロロエチレンカーボネート及びジフルオロビス(オキサラト)リン酸リチウムは、負極表面にLiCl-LiF無機塩及びビニレンカーボネートオリゴマーとを有する二重層構造を形成することができる。ビニレンカーボネートオリゴマーの一部は有機化合物であるため、柔軟性が高く、負極との界面でのコーティング効果がより好ましい。LiFの剛性と無機塩へのLiClの溶解度の低さにより、配合後の負極保護層(SEI膜)の安定性が確保され、これにより高温における電池の性能が向上する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021396000001
    Figure 2025021396000001
  • Figure 2025021396000002
    Figure 2025021396000002
  • Figure 2025021396000003
    Figure 2025021396000003
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte and a lithium ion battery for improving a gas generation problem of a lithium ion battery under high temperatures.SOLUTION: The non-aqueous electrolyte includes a non-aqueous organic solvent, lithium salt, and an additive. The additive includes chloroethylene carbonate and lithium difluoro(bis(oxalato))phosphate. By combining additives, a double-layer structure consisting of LiCl-LiF inorganic salt and vinylene carbonate oligomer can be formed on the surface of the negative electrode, and this provides an excellent coating effect at the interface with the negative electrode. The rigidity of LiF and the low solubility of LiCl in the inorganic salt ensure the stability of a negative electrode protective layer after mixing, thereby improving the performance of the battery at high temperatures.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of secondary batteries, and in particular to non-aqueous electrolytes and lithium ion batteries. [Background technology]

[0002] In recent years, with the popularity of cameras, mobile phones, watches, laptops, electric vehicles, etc., the demand for lithium-ion batteries has been increasing. Therefore, miniaturization, weight reduction, increased energy density, and extended service life have become the development trends in the battery product industry.

[0003] Electrolytes are an important component of lithium-ion batteries. They function to transport lithium ions between the positive and negative electrodes. The safety of the battery, the charge-discharge cycle performance, the rate performance, and the charge-discharge capacity of the battery are all closely related to the electrochemical properties of the electrolyte. Currently, the electrolytes widely used in lithium-ion batteries are generally those that use lithium hexafluorophosphate (LiPF6) as the electrolyte salt and a mixture of cyclic carbonate and chain carbonate as the organic solvent. However, such electrolytes have many defects. In particular, the negative electrode interface protection layer (SEI film) of lithium-ion batteries is prone to rupture and repair under high voltage, and electrochemical reactions between the electrolyte solvent and other added components are inevitable, resulting in the problem of gas generation.

[0004] In view of the above, there is an urgent need to develop new lithium-ion battery electrolytes to solve the above problems. Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above shortcomings of the prior art, the present invention provides a non-aqueous electrolyte and a lithium ion battery to improve the gassing problem of lithium ion batteries under high temperatures. [Means for solving the problem]

[0006] In order to achieve the above and other related objectives, the present invention provides a non-aqueous electrolyte comprising a non-aqueous organic solvent, a lithium salt, and an additive, the additive comprising chloroethylene carbonate and lithium difluorobis(oxalato)phosphate, the chloroethylene carbonate comprising a compound represented by the following structural formula: [ka]

[0007] wherein the R group is selected from a Cl group or a CCl group.

[0008] In one embodiment of the present invention, the content of chloroethylene carbonate in the non-aqueous electrolyte is 0.5% to 5% by mass.

[0009] In one embodiment of the present invention, the content of chloroethylene carbonate in the non-aqueous electrolyte is 1 to 2.5% by mass.

[0010] In one embodiment of the present invention, the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte is 0.5% to 2% by mass.

[0011] In one embodiment of the present invention, the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte is 0.5% to 1% by mass.

[0012] In one embodiment of the present invention, the conductivity of the non-aqueous electrolyte is 7.0 mS / cm to 12.5 mS / cm.

[0013] In one embodiment of the present invention, the structural formula of chloroethylene carbonate is as follows: [ka]

[0014] In one embodiment of the invention, the lithium salt comprises lithium hexafluorophosphate and / or lithium bis(fluorosulfonyl)imide.

[0015] In one embodiment of the present invention, the content of the lithium salt in the non-aqueous electrolyte solution is 8 to 20% by mass.

[0016] In one embodiment of the present invention, the non-aqueous organic solvent includes a cyclic carbonate and a chain carbonate. The cyclic carbonate includes one or both of ethylene carbonate and propylene carbonate. The chain carbonate includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0017] Another aspect of the present invention provides a lithium ion battery including a positive electrode sheet, a negative electrode sheet, a separator, and the above-described nonaqueous electrolyte. Effect of the Invention

[0018] The present invention introduces chlorine-containing organic additives, which are chloroethylene carbonate (ClEC) and lithium difluorobis(oxalato)phosphate (LiODFP), into the non-aqueous electrolyte. During the introduction process, chloroethylene carbonate and lithium difluorobis(oxalato)phosphate can form a bilayer structure with LiCl-LiF inorganic salt and vinylene carbonate oligomer on the surface of the negative electrode. Since a part of the vinylene carbonate oligomer is an organic compound, it has high flexibility and the coating effect at the interface with the negative electrode is more favorable. Due to the rigidity of LiF and the low solubility of LiCl in the inorganic salt, the stability of the negative electrode protective layer (SEI film) after mixing is ensured, thereby improving the performance of the battery at high temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will be described below with reference to specific examples. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific implementations. Various details of this specification can also be modified or changed in various ways based on different perspectives and applications without departing from the spirit of the present invention. In addition, the following embodiments and the characteristic parts in each embodiment may be combined as long as there is no contradiction between each embodiment. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments and are not intended to limit the scope of the present invention. In the following examples, test methods that do not specify specific conditions usually adopt conventional conditions or conditions recommended by each manufacturer.

[0020] For simplicity, the present invention expressly discloses only certain numerical ranges, and all points or individual values ​​between the endpoints of the ranges are included within the range. Thus, each point or single value can serve as its own lower or upper limit in combination with other points or single values, or in combination with other lower or upper limits, to form ranges not expressly recited.

[0021] The present invention provides a non-aqueous electrolyte and a lithium ion battery. The lithium ion battery includes the non-aqueous electrolyte of the present invention. Since chloroethylene carbonate and lithium difluorobis(oxalato)phosphate are introduced into the non-aqueous electrolyte, a bilayer structure having LiCl-LiF inorganic salt and vinylene carbonate oligomer can be formed on the negative electrode surface, which improves the coating effect and stability of the negative electrode interface film, and improves the performance of the lithium ion battery at high temperatures.

[0022] The non-aqueous electrolyte includes a non-aqueous organic solvent, a lithium salt, and an additive. The lithium salt and the additive are dissolved in the non-aqueous organic solvent. The additive includes a chlorine-containing organic additive and lithium difluorobis(oxalato)phosphate. The chlorine-containing organic additive includes chloroethylene carbonate, and the structural formula of chloroethylene carbonate is as follows: [ka]

[0023] In the formula, the R group is selected from a Cl group or a CCl group. In other words, the chloroethylene carbonate may be a compound represented by structural formula (1), a compound represented by structural formula (2), or a composition in which the compounds represented by structural formula (1) and structural formula (2) are mixed in any ratio. [ka]

[0024] Since both structural formula (1) and structural formula (2) contain a vinylene carbonate group and a chlorine-containing group, by mixing structural formula (1) and structural formula (2) with lithium difluorobis(oxalato)phosphate during the operation of the battery, a bilayer structure having LiCl-LiF inorganic salt and vinylene carbonate oligomer can be formed on the negative electrode surface, where the vinylene carbonate oligomer layer is an organic compound layer with high flexibility and good coating effect at the interface with the negative electrode. The rigidity of LiF and the low solubility of LiCl can ensure the stability of the negative electrode protective layer (SEI film) after mixing.

[0025] The chloroethylene carbonate is preferably a compound represented by structural formula (1). [ka]

[0026] As a result of the research, it was found that the combination of the compound represented by the structural formula (1) and lithium difluorobis(oxalato)phosphate has a higher production efficiency of LiCl-LiF composite inorganic salt and vinylene carbonate oligomer than the combination of the compound represented by the structural formula (2) and lithium difluorobis(oxalato)phosphate. Therefore, it is preferable that the chloroethylene carbonate is the compound represented by the structural formula (1).

[0027] In some embodiments, the content of the chloroethylene carbonate additive in the non-aqueous electrolyte is 0.5% to 5% by mass, such as 0.5%, 1%, 3%, 5%, etc. The content of the lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte is 0.5% to 2% by mass, such as 0.5%, 1.5%, 2%, etc. Furthermore, the content of the chloroethylene carbonate in the non-aqueous electrolyte is 1% to 2.5% by mass, such as 1.5%, 2%, 2.5%, etc. The content of the lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte is 0.5% to 1% by mass, such as 0.5%, 0.8%, 1.0%, etc. By adjusting the ratio of chloroethylene carbonate and lithium difluorobis(oxalato)phosphate, the conductivity of the electrolyte can be adjusted to 7.0 mS / cm to 12.5 mS / cm. Here, the conductivity of the electrolyte is not limited and can be adjusted within the above range, such as 7.0 mS / cm, 10 mS / cm, or 12 mS / cm.

[0028] It should be noted that both the chloroethylene carbonate and the lithium difluorobis(oxalato)phosphate of the present invention can be purchased through common commercial routes or can be prepared using conventional preparation methods in this field.

[0029] The lithium salt in the non-aqueous electrolyte serves as the electrolyte salt. When the lithium salt dissolves in the non-aqueous solvent, a large amount of active lithium ions are released, which improves the conductivity of the electrolyte. To obtain a better electrolyte, the lithium salt is usually adopted with the characteristics of low dissociation energy and high solubility. Due to the low dissociation energy, the electrolyte formed after the lithium salt dissolves has high conductivity, which achieves high battery speed. Due to the high solubility, there are enough lithium ions in the electrolyte for transportation, which improves stability. Therefore, the lithium salt does not react with other components when the battery operates at high voltage and high temperature. The excellent SEI film formation performance ensures that the electrolyte is not continuously consumed during subsequent cycles. In addition, it has an excellent passivation effect on the aluminum current collector, which can prevent the corrosion of the aluminum foil under high voltage. Such electrolyte is cost-effective and non-toxic and non-polluting.

[0030] In one example, the lithium salt may be selected from lithium hexafluorophosphate (LiPF6) and / or lithium bis(fluorosulfonyl)imide (LiFSI). That is, the lithium salt may be selected from lithium hexafluorophosphate alone, lithium bis(fluorosulfonyl)imide alone, or a composition of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. In another example, the lithium salt may be selected from lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium difluoro(oxalato)borate (LiDFOB), lithium bis(trifluoromethane)sulfonimide (LiTFSI), or lithium difluorophosphate (LiPF2O2). It is preferable that the lithium salt is selected from lithium hexafluorophosphate with better overall performance, or lithium hexafluorophosphate functions as the main component and is combined with other lithium salts added in appropriate amounts to improve the performance of the electrolyte through the composition using the combination. The concentration of the lithium salt can be set according to conventional selection in this field. In one example, the content of the lithium salt in the non-aqueous electrolyte is 8% to 20% by mass, for example, 8%, 12.5%, 15%, or 20%, etc.

[0031] The non-aqueous organic solvent can be selected from conventional combinations of solvents in the art. In the present invention, the non-aqueous organic solvent includes cyclic carbonates and linear carbonates. The cyclic carbonate includes one or both of ethylene carbonate (EC) and propylene carbonate (PC). For example, the cyclic carbonate can be ethylene carbonate, propylene carbonate, or a mixture of ethylene carbonate and propylene carbonate in any ratio. The linear carbonate includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). That is, the linear carbonate can be any of those listed above, such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate. The chain carbonate may be a combination of any two or three of the above-mentioned components, such as a combination of dimethyl carbonate and diethyl carbonate, a combination of diethyl carbonate and ethyl methyl carbonate, or a combination of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, etc. When the chain carbonate is a composition, the ratio of each component in the composition is not particularly limited, and they may be mixed in any ratio.

[0032] The non-aqueous electrolyte of the present invention can be manufactured according to a conventional manufacturing method. For example, first, mix and stir the non-aqueous organic solvent in a glove box, then add lithium salt, continue stirring until the lithium salt is completely dissolved, and finally add chloroethylene carbonate and lithium difluorobis(oxalato)phosphate and stir well. The nitrogen content in the glove box is 99.999%, the actual oxygen content in the glove box is 0.1 ppm, and the water content is 0.1 ppm.

[0033] A second aspect of the present invention provides a lithium ion battery. The battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the charge and discharge process of the battery, lithium ions are absorbed and released between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet and has a separating function. The electrolyte has a function of transmitting ions between the positive electrode sheet and the negative electrode sheet. The electrolyte is the non-aqueous electrolyte described above in the present invention. Since the non-aqueous electrolyte includes chloroethylene carbonate and lithium difluorobis(oxalato)phosphate, the mixture of the two can form a bilayer structure having LiCl-LiF inorganic salt and vinylene carbonate oligomer on the negative electrode surface, thereby ensuring the stability of the negative electrode protective layer (SEI film), and therefore providing both high and low temperature performance.

[0034] Specifically, the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector, and the positive electrode collector may be made of a material having good electrical conductivity and mechanical strength, such as aluminum foil. The positive electrode collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on one or both of the two facing surfaces of the positive electrode collector. The positive electrode active material layer includes a positive electrode material, a positive electrode conductive agent, and a positive electrode binder. The specific types of the positive electrode material, the positive electrode conductive agent, and the positive electrode binder are not particularly limited and can be selected by a person skilled in the art according to actual needs.

[0035] As an example, the positive electrode material can be selected from a ternary material and a lithium-containing phosphate. Specifically, the ternary material includes, but is not limited to, lithium nickel cobalt manganese oxide and lithium nickel cobalt manganese oxide doped with metal ions. The doping element is, for example, any one or more selected from Zr, Ti, Mo, Al, Sr, W, Y, Ta, Nb, Mg, and Ba. The lithium-containing phosphate includes, but is not limited to, lithium manganese iron phosphate, lithium iron phosphate, lithium manganese phosphate, etc. The positive electrode binder is, for example, selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc. The positive electrode conductive agent is, for example, one or more selected from carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., mixed in any ratio.

[0036] The positive electrode sheet can be manufactured according to a method known in the art. As an example, a positive electrode material, a positive electrode conductive agent, and a positive electrode binder are dispersed in a solvent (e.g., N-methylpyrrolidone, abbreviated as NMP) to form a uniform positive electrode slurry. The positive electrode slurry is applied onto a positive electrode current collector, and a positive electrode sheet is obtained through processes such as drying and cold pressing. The ratio of each component in the positive electrode slurry can be set with reference to conventional ratios, and the present invention is not limited thereto.

[0037] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be made of a material having good electrical conductivity and mechanical strength, such as copper foil. The negative electrode current collector has two surfaces facing each other in the thickness direction of the negative electrode current collector, and the negative electrode active material layer is disposed on one or both of the two facing surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode material, a negative electrode conductive agent, a negative electrode binder, and a thickener. The specific types of the negative electrode material, the negative electrode conductive agent, and the negative electrode binder are not particularly limited. Materials known in the art that can be used for lithium ion batteries can be adopted, and can be selected by a person skilled in the art according to actual needs.

[0038] Preferably, the negative electrode material is a silicon-containing negative electrode material such as elemental silicon, silicon oxygen compounds, and silicon carbon compounds, and chloroethylene carbonate (ClEC) and lithium difluorobis(oxalato)phosphate form a bilayer structure with LiCl-LiF complex inorganic salt and vinylene carbonate oligomer on the silicon negative electrode surface, so that a better coating effect can be obtained at the interface with the silicon negative electrode. The rigidity of LiF and the low solubility of LiCl can ensure the stability of the silicon negative electrode protective layer after mixing. The negative electrode conductive agent is one selected from carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more of them in any ratio is used. The negative electrode binder is selected from one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), and styrene butadiene rubber (SBR), or a mixture of multiple compositions in any ratio. The thickener is selected from carboxymethyl cellulose (CMC).

[0039] The negative electrode sheet can be manufactured according to a method known in the art. For example, a negative electrode material, a negative electrode binder, a thickener, and a negative electrode conductive agent are dispersed in deionized water to form a uniform negative electrode slurry. The negative electrode slurry is applied onto a negative electrode current collector, and a negative electrode sheet is obtained through drying, cold pressing, and other processes. The ratio of each component in the negative electrode slurry can be set with reference to conventional ratios, and the present invention is not limited thereto.

[0040] The separator is selected from conventional materials used in the field, such as a porous PE film, etc. The thickness of the separator is 9 μm to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.

[0041] The battery is assembled according to conventional methods. After preparation is complete, the negative electrode sheet, separator, and positive electrode sheet are stacked in order, and then inserted into an aluminum laminate film to form a shell cell, which is then baked at 80°C to remove moisture. The prepared electrolyte is injected into the shell cell, which is then sealed to obtain a lithium-ion battery product.

[0042] The technical solution of the present invention will be described in detail below through some specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by conventional methods in the art, and the equipment used in the examples are all commercially available.

[0043] Example 1

[0044] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 3:5:2 to prepare a non-aqueous organic solvent. Dried lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent and mixed uniformly, and then the compound represented by structural formula (1) and lithium difluorobis(oxalato)phosphate (LiODFP) were added and mixed uniformly to prepare a non-aqueous electrolyte. The content of lithium hexafluorophosphate in the non-aqueous electrolyte was 12.5% ​​by mass percentage, the content of the compound represented by structural formula (1) in the non-aqueous electrolyte was 1% by mass percentage, and the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte was 0.7% by mass percentage.

[0045] Example 2

[0046] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 3:5:2 to prepare a non-aqueous organic solvent. Dried lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent and mixed uniformly, and then the compound represented by structural formula (2) and lithium difluorobis(oxalato)phosphate (LiODFP) were added and mixed uniformly to prepare a non-aqueous electrolyte. The content of lithium hexafluorophosphate in the non-aqueous electrolyte was 12.5% ​​by mass, the content of the compound represented by structural formula (2) in the non-aqueous electrolyte was 1.5% by mass, and the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte was 2% by mass.

[0047] Example 3

[0048] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 3:5:2 to prepare a non-aqueous organic solvent. Dried lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent and mixed uniformly, and then the compound represented by structural formula (1) and lithium difluorobis(oxalato)phosphate (LiODFP) were added and mixed uniformly to prepare a non-aqueous electrolyte. The content of lithium hexafluorophosphate in the non-aqueous electrolyte was 12.5% ​​by mass percentage, the content of the compound represented by structural formula (1) in the non-aqueous electrolyte was 0.5% by mass percentage, and the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte was 0.7% by mass percentage.

[0049] Example 4

[0050] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 3:5:2 to prepare a non-aqueous organic solvent. Dried lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent and mixed uniformly, and then the compound represented by structural formula (1) and lithium difluorobis(oxalato)phosphate (LiODFP) were added and mixed uniformly to prepare a non-aqueous electrolyte. The content of lithium hexafluorophosphate in the non-aqueous electrolyte was 12.5% ​​by mass, the content of the compound represented by structural formula (1) in the non-aqueous electrolyte was 2.5% by mass, and the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte was 0.7% by mass.

[0051] Example 5

[0052] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 3:5:2 to prepare a non-aqueous organic solvent. Dried lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent and mixed uniformly, and then the compound represented by structural formula (1) and lithium difluorobis(oxalato)phosphate (LiODFP) were added and mixed uniformly to prepare a non-aqueous electrolyte. The content of lithium hexafluorophosphate in the non-aqueous electrolyte was 12.5% ​​by mass percentage, the content of the compound represented by structural formula (1) in the non-aqueous electrolyte was 5% by mass percentage, and the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte was 0.7% by mass percentage.

[0053] Example 6

[0054] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 3:5:2 to prepare a non-aqueous organic solvent. Dried lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent and mixed uniformly, and then the compound represented by structural formula (1) and lithium difluorobis(oxalato)phosphate (LiODFP) were added and mixed uniformly to prepare a non-aqueous electrolyte. The content of lithium hexafluorophosphate in the non-aqueous electrolyte was 12.5% ​​by mass percentage, the content of the compound represented by structural formula (1) in the non-aqueous electrolyte was 1% by mass percentage, and the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte was 0.5% by mass percentage.

[0055] Example 7

[0056] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 3:5:2 to prepare a non-aqueous organic solvent. Dried lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent and mixed uniformly, and then the compound represented by structural formula (1) and lithium difluorobis(oxalato)phosphate (LiODFP) were added and mixed uniformly to prepare a non-aqueous electrolyte. The content of lithium hexafluorophosphate in the non-aqueous electrolyte was 12.5% ​​by mass percentage, the content of the compound represented by structural formula (1) in the non-aqueous electrolyte was 1% by mass percentage, and the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte was 1.2% by mass percentage.

[0057] Example 8

[0058] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 3:5:2 to prepare a non-aqueous organic solvent. Dried lithium hexafluorophosphate (LiPF6) was added to the non-aqueous organic solvent and mixed uniformly, and then the compound represented by structural formula (1) and lithium difluorobis(oxalato)phosphate (LiODFP) were added and mixed uniformly to prepare a non-aqueous electrolyte. The content of lithium hexafluorophosphate in the non-aqueous electrolyte was 12.5% ​​by mass, the content of the compound represented by structural formula (1) in the non-aqueous electrolyte was 1% by mass, and the content of lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte was 2% by mass.

[0059] Comparative Example 1

[0060] The difference between this comparative example and Example 1 is that lithium difluorobis(oxalato)phosphate (LiODFP) is not added in this comparative example.

[0061] Comparative Example 2

[0062] The difference between this comparative example and Example 1 is that in this comparative example, the compound represented by structural formula (1) is not added.

[0063] Comparative Example 3

[0064] The difference between this comparative example and Example 1 is that in this comparative example, the compound represented by structural formula (1) and lithium difluorobis(oxalato)phosphate (LiODFP) are not added.

[0065] Comparative Example 4

[0066] The difference between this comparative example and Example 1 is that in this comparative example, the amount of the compound represented by structural formula (1) added is 7%, and the amount of lithium difluorobis(oxalato)phosphate (LiODFP) added is 5%.

[0067] Comparative Example 5

[0068] The difference between this comparative example and Example 1 is that in this comparative example, the amount of the compound represented by structural formula (1) added is 7%, and lithium difluorobis(oxalato)phosphate (LiODFP) is not added.

[0069] Comparative Example 6

[0070] The difference between this comparative example and Example 1 is that in this comparative example, the compound represented by structural formula (1) is not added, and the amount of lithium difluorobis(oxalato)phosphate (LiODFP) added is 5%.

[0071] The electrolyte solutions prepared in Examples 1 to 8 and Comparative Examples 1 to 6 were each used in a lithium ion battery to verify the effectiveness of chloroethylene carbonate and lithium difluorobis(oxalato)phosphate. The process for producing a lithium-ion battery is as follows.

[0072] (1) Positive electrode sheet: LiNi 0.9 Co 0.05 Mn 0.05 A positive electrode active material selected from O2, a conductive agent selected from acetylene black, and a binder selected from polyvinylidene fluoride were dissolved in N-methylpyrrolidone (NMP) in a mass ratio of 95:3:2, and the uniformly mixed slurry was applied onto an aluminum foil, followed by drying, rolling, and cutting to obtain a positive electrode sheet.

[0073] (2) Negative electrode sheet: A negative electrode active material selected from a silicone compound, a conductive agent selected from acetylene black, a thickener selected from CMC-Li, and a binder selected from SBR were mixed in a mass ratio of 96.4:1:1.2:1.4, and then deionized water was added and mixed uniformly and thoroughly to obtain a negative electrode slurry. Next, deionized water was added to the negative electrode slurry and mixed uniformly, and the mixture was applied onto a copper foil, dried, rolled, and cut to obtain a negative electrode sheet.

[0074] (3) Separator: A porous PE film with a thickness of 11 um was selected as the separator.

[0075] (4) Battery assembly: The prepared positive electrode sheet, separator, and negative electrode sheet were laminated in order so that the separator was placed between the positive electrode sheet and the negative electrode sheet to perform the insulating function. The laminated material was placed in an aluminum plastic film to obtain a dry battery cell. The dry battery cell was baked at 80°C to remove moisture. The prepared electrolyte was injected into the dry battery cell and sealed to obtain a lithium-ion battery.

[0076] Performance tests were carried out on the lithium ion batteries assembled using the electrolyte solutions of Examples 1 to 8 and Comparative Examples 1 to 6. The test results are shown in Table 1. The test method was as follows.

[0077] (1) Initial impedance DCR at 25°C:

[0078] The thermostat temperature was set to 25°C and the battery was left to stand for 10 minutes. The battery was charged to 4.25V at a constant current of 0.33C, then charged to 0.05V at a constant current of 4.25V, and left to stand for 30 minutes. The battery was then discharged to 2.5V at a constant current of 0.33C. Two cycles of charging and discharging were performed at 0.33C, and the final discharge capacity was recorded as C0. After leaving the battery to stand for 30 minutes, the battery was discharged to 50% C0 at 0.33C, the SOC of the battery cell was adjusted to 50%, and the battery was left to stand for 1 hour, and the static terminal voltage was recorded as V1. The battery was discharged at a constant current of 4C0 for 30 minutes, the terminal voltage was recorded as V2, the current as I, and the DCR=(V1-V2) / I was calculated.

[0079] (2) Volume expansion rate after storage at high temperature of 60℃ for 30 days:

[0080] At 25°C, the lithium-ion battery was charged at a constant current of 1C to 4.25V, then at a constant voltage to a current of 0.05C. The volume of the lithium-ion battery was tested and recorded as X0. The fully charged battery was then stored in an oven at 60°C for 30 days. The volume after storage was tested and recorded as X1. The volume expansion ratio of the lithium-ion battery before storage was calculated by the following formula:

[0081] Volume expansion rate (%) = (X1-X0) / X0 × 100%.

[0082] [Table 1]

[0083] Comparing Example 1 and Example 2, it can be seen that the combination of the compound represented by structural formula (1) and LiODFP can achieve significantly better effects in terms of initial impedance and gas storage performance than the combination of the compound represented by structural formula (2) and LiODFP. This indicates that the compound represented by structural formula (1) has better efficiency in forming LiCl-LiF complex inorganic salt and vinylene carbonate oligomer.

[0084] Comparing Examples 1, 3 to 5, when a certain amount of LiODFP is added, as the amount of the compound represented by structural formula (1) increases, the initial impedance first decreases and then increases, and the amount of gas stored at high temperature decreases and then increases, so that it can be seen that the optimal amount of the compound represented by structural formula (1) is about 1%. In this way, the uniformity and appropriate thickness of the SEI formed can be ensured. If the amount of the compound represented by structural formula (1) is too small, the amount of the SEI film formed is small, and the negative electrode interface cannot be completely covered. Also referring to Comparative Examples 4 and 5, if the amount of the compound represented by structural formula (1) is too large, the SEI film formed becomes thick, which is not favorable for lithium ion transport and stability at high temperatures.

[0085] Comparing Examples 1, 6 to 8, it can be seen that, when the amount of the compound represented by structural formula (1) added is constant, as the amount of LiODFP added increases, the initial impedance first decreases and then increases, and the gas storage amount at high temperatures first decreases and then increases. This indicates that the optimal amount of LiODFP is about 0.7%. If the amount of LiODFP added is too much (see Comparative Examples 4 and 6) or too little, the stability of the SEI film decreases, which adversely affects the performance of the battery cell.

[0086] Comparing Example 1, Comparative Example 1, and Comparative Example 2, when the compound represented by structural formula (1) and LiODFP are added to the electrolyte simultaneously, both the initial impedance and the gas storage amount at high temperature are lower than when only one additive is added. This indicates that only when two additives are present simultaneously, the negative electrode surface can be coated with a bilayer structure having LiCl-LiF inorganic salt and vinylene carbonate oligomer, and only one additive alone cannot form the corresponding structure, so the effect is poor.

[0087] The present invention introduces chloroethylene carbonate and lithium difluorobis(oxalato)phosphate into the non-aqueous electrolyte to form a bilayer structure of LiCl-LiF inorganic salt and vinylene carbonate oligomer on the surface of the negative electrode, thereby improving the coating effect and stability of the negative electrode interface film and improving the performance of lithium ion batteries at high temperatures. Therefore, the present invention effectively overcomes some practical problems in the prior art, has high utility value, and is of great practical significance. [Industrial Applicability]

[0088] Furthermore, the nonaqueous electrolyte and the lithium ion battery containing the same provided by the present invention can be used in the field of electronics, and have high industrial applicability.

[0089] The above-mentioned embodiment is illustrative of the principle and effect of the present invention, but is not intended to limit the present invention. Anyone familiar with this technology can modify or change the above-mentioned embodiment without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person having ordinary knowledge in the technical field without departing from the spirit and technical idea disclosed in the present invention are also intended to be included in the scope of the claims of the present invention.

Claims

1. 1. A non-aqueous electrolyte solution comprising a non-aqueous organic solvent, a lithium salt, and an additive, the additive comprising chloroethylene carbonate and lithium difluorobis(oxalato)phosphate, the chloroethylene carbonate comprising a compound represented by the following structural formula: 【Chemistry 1】 In the formula, the R group is a Cl group or a CCl 3 is selected from the group.

2. The content of the chloroethylene carbonate in the nonaqueous electrolyte is 0.5% to 5% by mass. The nonaqueous electrolyte according to claim 1 .

3. The content of the chloroethylene carbonate in the nonaqueous electrolyte is 1% to 2.5% by mass. The nonaqueous electrolyte according to claim 2 .

4. The content of the lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte is 0.5% to 2% by mass. The nonaqueous electrolyte according to claim 1 .

5. The content of the lithium difluorobis(oxalato)phosphate in the non-aqueous electrolyte is 0.5% to 1% by mass. The nonaqueous electrolyte according to claim 4.

6. The conductivity of the non-aqueous electrolyte is 7.0 mS / cm to 12.5 mS / cm. The nonaqueous electrolyte according to claim 1 .

7. The structural formula of the chloroethylene carbonate is as follows: The nonaqueous electrolyte according to claim 1 . 【Chemistry 2】

8. The lithium salt includes lithium hexafluorophosphate and / or lithium bis(fluorosulfonyl)imide, and the content of the lithium salt in the nonaqueous electrolyte is 8% to 20% by mass. The nonaqueous electrolyte according to claim 1 .

9. The non-aqueous organic solvent includes a cyclic carbonate and a chain carbonate, the cyclic carbonate includes one or both of ethylene carbonate and propylene carbonate, and the chain carbonate includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. The nonaqueous electrolyte according to claim 1 .

10. A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator, and the nonaqueous electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2000208169A

  • Battery

    JP2006190635A

  • Nonaqueous electrolyte secondary battery

    JP2014011023A

  • Lithium ion secondary battery

    JP2024087469A